ALISIS SIFAT MEKANIK RANTAI TIPE 428 PADA SEPEDA MOTOR PRODUK YAMAHA MX135 - Brilliant Davidson; Markus Karamoy Umboh; Tritiya Arungpadang (JURNAL POROS TEKNIK MESIN UNSRAT, 2021)
The motorcycle chain is one of the most important parts of the motor which has a function to transmit power from the engine to the wheels. In this study, an analysis of the mechanical properties and chemical composition of the plates and pins of the Yamaha MX 135 type 428 motorcycle chain and other motorcycle chain products was carried out. The methodology used is hardness testing, microstructure testing and chemical composition testing on the two motor chain products and comparing them with the standard.The results obtained show that the chain plate hardness value for Yamaha products is 44.35HRC and other products of 44.4 HRC have exceeded the SAE 1050 hardness standard of 30 HRC. The hardness value of the Yamaha motorcycle chain pin is 427 HB and the motorcycle chain pin of other products is 428 HB which has met the AISI 15B25 standard of 131 HB. Thus, the value of the tensile strength of both plate and chain pins for Yamaha motorcycles and other products obtained from the conversion of hardness values also exceeds the set standards. The results of microstructure testing for plates and pins of motorcycle chains for Yamaha products and other products contain ferrite and pearlite phases with uneven distribution. The results of the chemical composition test show that the Yamaha motorcycle chain plate has met the SAE 1050 standard while the other product motorcycle chain has a C element content of 1.44% exceeding the standard which is 0.48-0.55%. In the motorcycle chain pin, Yamaha products have a C content of 0.4% and in other products it has a C content of 0.43%, which is greater than the AISI 15B25 standard of 0.22-0.3% C.